Dielectric and Flash-over Characteristics of the ±1100kV Valve Side Converter Transformer Bushing with SF6 Gas Insulation. Issue 1 (June 2021) - Shiling, Zhang; Wei, Song
Abstract: The ±1100kV high voltage capacitor filled SF6 gas bushing is an important equipment to realize the electrical connection between the converter transformer and the valve tower. The paper mainly discusses the design of the external and internal insulation structure. The research content is divided into four parts, the actual operating environment and the characteristics of the voltage and current waveform of converter transformer bushing are discussed. The design and analysis of the hollow composite insulator, corona ring and tail end of the bushing have been done. The main insulation structure of bushing has been designed by the equal margin method, and simulation and analysis of the multi-physical field have been done. The three dimensional electric field simulation model has been set up to calculate and analyze the external insulation performance of the bushing. The results show that the main insulation of the bushing is fit to the capacitance structure, the maximum axial field strength of the bushing is 0.62kV·mm −1, and the end of the bushing should be equipped with apple type corona ring. The insulation distance of the hollow composite insulator is designed as 7490mm. The insulation distance of the bushing tail is designed as 3110mm. In the actual operating environment, the maximum field strength of the corona ring appears on the lower end surface, and the value is 2386V·mm −1 . The results of the paper can provide the theoretical basis for the design of the external insulation of the converter transformer bushing used in the HVDC transmission project.